Analysis Of Implementation Of Discipline In The Class Of Integrated Social Science (History) Learning In Class Viii First Sekadau Junior High School, Sekadau District - Muhammad Sadikin (JURNAL HISTORICA, 2023)
The purpose of this study was to analyze the application of discipline in class to integrated Social Science learning in class VIII SMP Negeri 1 Sekadau Hulu, Sekadau Regency with research sub-focus: 1). What is the teacher's strategy for upholding discipline in the classroom in learning Integrated Social Sciences (History); 2). How is the teacher's technique for fostering discipline in the classroom in learning Integrated Social Sciences (History); 3). What are the factors that become obstacles to the application of discipline in the classroom in learning Integrated Social Sciences (History); 4). How do teachers deal with disciplinary violations in the classroom in Integrated Social Sciences (History) lessons? This research uses descriptive method in the form of survey research. The research was conducted at Sekadau Hulu State Junior High School 1, Sekadau District. The results of the study show that the application of discipline in the classroom has generally been going well. This can be seen from the learning activities that take place effectively and in a conducive learning atmosphere. Where educational interaction between teachers and students goes well and students are actively involved during teaching and learning activities taking place in the classroom. Keyword: Application of discipline, Social Sciences, Junior High School